2020
DOI: 10.3390/ijms21228464
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Responses to Low-Intensity Radiation of Tritium

Abstract: The present study considers a possible role of enzymatic reactions in the adaptive response of cells to the beta-emitting radionuclide tritium under conditions of low-dose exposures. Effects of tritiated water (HTO) on the reactions of bacterial luciferase and NAD(P)H:FMN-oxidoreductase, as well as a coupled system of these two reactions, were studied at radioactivity concentrations ≤ 200 MBq/L. Additionally, one of the simplest enzymatic reactions, photobiochemical proton transfer in Coelenteramide-containing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 57 publications
1
14
0
Order By: Relevance
“…Previously [ 6 , 16 , 17 ], we found correlations between the ROS content and bacterial bioluminescence intensity in tritiated water and thus suggested the involvement of ROS in the activation of bacterial physiological functions under exposure to the beta-emitting radionuclide tritium. A question of special interest is: are ROS effects responsible for the bioeffects of other radionuclides with differing characteristics of radioactive decay?…”
Section: Introductionsupporting
confidence: 63%
See 3 more Smart Citations
“…Previously [ 6 , 16 , 17 ], we found correlations between the ROS content and bacterial bioluminescence intensity in tritiated water and thus suggested the involvement of ROS in the activation of bacterial physiological functions under exposure to the beta-emitting radionuclide tritium. A question of special interest is: are ROS effects responsible for the bioeffects of other radionuclides with differing characteristics of radioactive decay?…”
Section: Introductionsupporting
confidence: 63%
“…In our previous studies, we demonstrated the advantages of the bacteria-based and enzyme-based bioluminescent bioassays to monitor low-dose effects of radionuclide solutions [ 12 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ] and gamma radiation [ 22 ]. It can be noted that in 2003 the luminous marine bacteria were applied to study the toxicity of radiation for the first time [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Photosystem II responses of tomato leaflets to B. cinerea inoculation can be described as a time-dependent hormetic response ( Figure 8 ) in terms of “stress defense response” and “toxicity” [ 76 , 80 ]. Activation by a low-dose effect or short-time exposure is a common phenomenon that is associated with the term “hormesis”, typically indicating a positive biological response [ 13 , 44 , 55 , 81 , 82 , 83 , 84 , 85 , 86 ]. There are published studies reporting a time-dependent hormesis [ 55 , 82 ], but it is only recently that analysis has been made regarding the features of hormesis as a function of time [ 13 , 81 , 82 ], and according to our data, under biotic stress.…”
Section: Discussionmentioning
confidence: 99%